The Performance of Plastic Bubble Wrap (PBW) as Coarse Aggregate - Faris Izwan Shah Afzainizam; Adnan, Suraya Hani (Progress in Engineering Application and Technology, 2024)
This research investigates the effects of incorporating plastic bubble wrap (PBW) as a replacement for traditional coarse aggregates in concrete mixtures. The study aims to assess how this unconventional material influences both the compressive strength and density of the resulting concrete. The experimental approach involves varying percentages of PBW substitution for coarse aggregates in concrete mix designs. Compressive strength tests are conducted on standard cubes, while density measurements are taken to evaluate the structural and mass properties of the concrete. Preliminary findings indicate that the inclusion of PBW has a noticeable impact on both compressive strength and density. The results suggest potential benefits in terms of reduced weight and enhanced insulation properties, which may have implications for certain construction applications. This research contributes to the ongoing exploration of alternative materials in concrete production, offering insights into the feasibility and performance of plastic bubble wrap as a substitute for conventional coarse aggregates. The outcomes of this study may have implications for sustainable construction practices and the utilization of recycled materials in the concrete industry. Further analysis and exploration of the long-term durability and structural characteristics of such concrete formulations are recommended for a comprehensive understanding of their practical applicability.